Presumed post‐traumatic ocular chondrosarcoma with intrathoracic metastases in a cat. (3rd October 2017) - Moreira, Matheus V. L.; de Andrade, Maria C.; Fulgêncio, Gustavo O.; Langohr, Ingeborg M.; Ecco, Roselene
Abstract: An indoor‐only, 5‐year‐old, spayed female domestic shorthair cat presented for an ophthalmic examination of the left eye. An intraocular tumor with secondary glaucoma and blindness was diagnosed; the globe was enucleated and sent for histopathological examination. Gross examination revealed a solid white mass filling the entire vitreous space and replacing the iris and ciliary body. The lens and retina appeared to be similarly replaced by the neoplasm. Histological examination revealed a complete loss of the internal ocular structures, with a ruptured capsule as the only remnant of the lens within an extensive malignant mesenchymal neoplastic cell proliferation. The cells were polygonal, with well‐defined cytoplasmic borders and abundant weakly basophilic cytoplasm, embedded within the islands of chondroid matrix. No neoplastic invasion of the sclera was apparent. The animal died 6 months after the enucleation due to respiratory distress. Gross examination revealed numerous firm, white to tan nodular masses with smooth to mildly irregular surfaces dispersed throughout the parietal pleura, thoracic surface of the diaphragm, tracheobronchial and mediastinal lymph nodes, pericardium, and lungs. On cross‐section, the neoplastic nodules were solid and variably translucent, resembling hyaline cartilage. Histologically, these nodules were similar to the neoplasm identified earlier in the left globe. Metastasis of post‐traumatic ocular chondrosarcoma has not yet been described in cats. This is therefore believed to be the first report of metastases of this type of neoplasm in cats. This case adds to the limited set of data on the outcome of this type of tumor.